Reflexiones sobre la utilidad de la novela histórica como herramienta de difusión y pedagógica - Martínez, Evaristo C. (Acta Hispanica, 2017)
The literary genre of the novel, besides being an element of entertainment, can also be a good useful for scientific dissemination. At this point, clearly it could turn into a pleasant tool and helps to reconstruct the essence of past times, having a greater projection in the field of History as long as it meets certain and elementary cases of rigor.